“BETA TANGGUH” : SELF-COMPASSION IN SURVIVORS OF DISFUNCTIONAL FAMILY - Ardhana, Adetiya Kusuma; Wijaya, R. Pasifikus Ch; Manafe, Rizky Pradita (Journal of Health and Behavioral Science, 2023)
Dysfunctional families are the originators of complex problems, so it is important for individual survivors of dysfunctional families to have self-compassion in themselves. This study aims to describe and provide an overview related to self-compassion in dysfunctional family survivors, and can provide an overview related to self-compassion by looking at aspects: self-kindness, self-judgment, common humanity, isolation, mindfulness, and over-identification. This study uses a qualitative method. The data collection technique used in this study was using the Photovoice method (photos tell stories). After that, participants were given digging questions in the form of interviews. The interview method used is in-depth interviewing. while the data analysis technique used by researchers in this study is Thematic Analysis. Participants were 5 survivors of dysfunctional families with inadequate parenting types, authoritarian parents, parents with violent behavior, controlling parents, and alcoholic parents. As a result, three main themes were found, namely vulnerabilities experienced by survivors of dysfunctional families, psychological wounds, and self-compassion. Participants in this study tend to have good self-compassion. This is illustrated by the ability of self-kindness, mindfulness, forgiveness and common humanity that have been developed by the participants of dysfunctional family survivors.